Pengaruh Peran Gender Dan Stres Kerja Terhadap Kinerja Perawat Di Rumah Sakit Umum Daerah Tarakan Provinsi Kalimantan Utara - Dina Fathonah; Syahran; Andriyansah (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The Tarakan Regional General Hospital, North Kalimantan was originally established in 1947 with the status of the Swatantra Regency Government of the Bulungan Regency with a Class D Hospital. This establishment aims to provide adequate health care facilities for the general public in the Tarakan island environment. The sample was 210 female nurses. conduct analysis to meet normality test requirements, descriptive statistics, perform multiple linear regression analysis and T test to answer hypotheses. In the gender role variable, the regression coefficient is 0.429 with a value of t = 7.213 with p = 0.000 or p <0.05. That is, some gender roles have a positive and significant influence on nurse performance. Thus, the H1 hypothesis can be accepted. In the work stress variable regression coefficient obtained -0.272 with a value of t = -4.726 with p = 0.000 or p <0.05. This means that work stress partially has a negative and significant effect on nurse performance. Thus, the H2 hypothesis can be accepted.